Arquiteturas metalo-supramoleculares em derivados de aroilbistioureias - Wioppiold, Thomaz Arruda (2018)
This work presents the synthesis and characterization of twenty-six compounds divided into two main groups. The first one approaches compounds containing the oxidorhenium(V) {ReO}3+ moeity and the ligands benzoyl(N,N-diethylthiourea) and isophthaloylbis(N,N-diethylthiourea) in single exchange reactions with triorganylsilanols (Me3SiOH and Ph3SiOH). The complexes synthesized from the precursor (nBu4N)[ReVOCl4] with BzHtuEt2 ligand lead to the formation of discrete molecules where the silanolato ligands are in the trans configuration to the oxido ligand. In contrast, the binuclear complexes formed with bipodal ligand isoph(HtuEt2)2 lead to the formation of two distinguished complexes. In the structure containing the trimethylsilanolato the syn isomer occurs, whereas the use of the bulky ligand triphenylsilanolato leads to formation of the anti isomer due to its steric effect. On the other hand, the second group involves the metallo-supramolecular compounds prepared from the coordination of the ligand 2,5-furanoylbis(N,N-diethylthiourea) with manganese(II), zinc(II) and indium(III). The manganese(II) atom is the most versatile for the construction of both [Mn2(L1)2] and [Mn2(L1)3]2- systems, which are used as hosts for different cations (Na+, K+, Rb+, Cs+, Tl+, Sr2+ and Ba2+). The structures of the metallacoronands [Mn2(L1)2] demonstrate the influence of the solvent in which the compounds are crystallized. The compound containing a DMSO molecule coordinated to the metal centers forms a discrete binuclear complex, while the one containing MeOH molecules as a coligand forms a one-dimensional pseudopolymer due to intermolecular hydrogen bonds. The inclusion of the Na+, Rb+, Cs+ and Tl+ ions in the prior structures in the presence of the acetate anion leads to the formation of the metallacoronates {M Ì [Mn2(L1)2]}(OAc)}n, which are organized as coordination polymers with unidimensional growth, where the acetates act as a bridge ligand between the units. It is not possible to obtain this type of structure with the K+ ion due to the formation of the metalacriptate (Et3NH){K Ì [Mn2(L1)2]}3, considering the template effect that the potassium cation exerts on these structures independent of the stoichiometry used. Complexes with three aroylbistioureas have also been obtained, in which the H3O+, Rb+, Sr2+ and Ba2+ ions are encapsulated. The reactions of the ligand H2L1 with zinc(II) acetate and Na+, K+ or Cs+ ions leads to the formation of three metallacoronates with different topologies. From the use of a trivalent metal such as indium(III) it’s possible to construct metallacrylates [In2(L)3] with the ligands H2L1 and 2,5- thiophenedicarbonylbis(N,N-diethylthiourea) (H2L2), which has a sulfur as the heteroatom in the spacer group. The inclusion of NH4 + and K+ ions in {M Ì [In2(L1)2]}3} systems is identified only in the ligand containing the furan spacer group. Mixed metal complexes are also identified when the metals used can be distinguished by the ligands in systems {K Ì [MnIIMIII(L1)2]}3. The compounds were suitably characterized by single crystal X-ray diffraction, as well as complementary analyzes such as elemental analysis, infrared spectroscopy, high resolution mass spectrometry and nuclear magnetic resonance spectroscopy when appropriate.